Issues in location based marketing: a review of literature - Jaradat, Ahmad; Mohamad Ali, Noor Azian; Asadullah, Ahmad; Ebrahim, Seyed (IJSRP.ORG, 2015)
Location based marketing has clearly become a primary element in today’s business. The main objective of this paper is to analyse such a growing phenomenon of using such location services by both marketers and customers, providing some motivations and factors that drive both parties to use these services. In addition, some popular applications in this field are mentioned as a real world example to provide deeper understanding on how such applications can facilitate our lives. Finally, an analysis on the issues regarding this topic is made which covers an expected problem in some applications as well as other issues related to the consumers and companies.